P1-S1.10 Microbiological surveillance for sexually transmitted infections in Windhoek and Oshakati, Namibia (2007). (10th July 2011) - Tobias, S; Shonhiwa, S; Norbert, F; Oke, O; Ndjavera, C; Chikukwa, S; Radebe, F; Lewis, D
Abstract : Background: A microbiological survey was undertaken to enable review of Namibia's syndromic management-based STI treatment guidelines (1999). Methods: This Government-approved survey took place at Katutura Health Centre (Windhoek) and Oshakati Intermediate Hospital over 9 months in 2007. Consecutive patients with urethral discharge (UDS), vaginal discharge (VDS) and genital ulcer (GUS) syndromes gave verbal consent to provide anonymous samples for the following tests—(i) real-time PCR (RT-PCR) for Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (TV), Mycoplasma genitalium (MG) (UDS, urethral swabs; VDS, endocervical swabs) (ii) RT-PCR detection of herpes simplex virus (HSV), Treponema pallidum (TP), Haemophilus ducreyi (HD), Chlamydia trachomatis L1-L3 (LGV) (ulcer swabs), (iii) Giemsa staining of ulcer smears for granuloma inguinale (GI), (iv) Gram staining of vaginal smears for Candida (CA) and bacterial vaginosis (BV), (v) NG culture and determination of ciprofloxacin and ceftriaxone minimum inhibitory concentrations (MIC) by E test (urethral swabs), and (vi) HIV ELISA (blood). All patients were provided with STI syndromic treatment, offered same-day HIV counselling and testing, and partner notification was discussed. Data analysis was performed in STATA v10 and the χ 2 test used to assess difference by survey site. Results: 199 UDS, 200 VDS and 199 GUS episodes were surveyed among 598 patients (293, Windhoek; 305, Oshakati). The relative prevalence of pathogens/conditions by syndrome was—(i) UDS—NG 87% (173), CT 9% (18), TV 5% (9), MG 2% (4), (ii) VDS—NG 5% (9), CT 8% (15), TV 15% (29), MG 4% (8), BV 65% (127), CA 17% (33), and (iii) GUS—HSV 49% (97), TP 3% (5), LGV 2% (2), GI 0.5% (1), HD 0% (0). Syndrome-specific HIV prevalence was 36% (62) for UDS, 29% (57) for VDS and 53% (91) for GUS. Ciprofloxacin resistance (MIC=1) was detected in 28 (24%) of 118 viable NG isolates; all isolates were deemed susceptible to ceftriaxone. Ciprofloxacin resistance was significantly higher in Oshakati compared to Windhoek (48% vs 5%, p<0.001). Conclusions: The survey highlighted the importance of gonorrhoea, genital herpes, HIV-coinfection and, in Oshakati, the high prevalence of ciprofloxacin resistant NG. As a result of this survey, Namibia's STI guidelines were revised in 2008 by adding acyclovir to existing GUS treatment and replacing ciprofloxacin with oral cefixime as treatment for presumptive gonorrhoea.